Bridging veins: an analysis of surgical anatomy and histology correlated with interhemispheric approaches - Ye, Yuanliang; Lan, TianCai; Zeng, Xiangbo; Yang, Jianqing; Wei, Ruixiang; Zhu, Jiale; Liu, Moukun; Zhu, Xiaowen (Frontiers in Neuroanatomy, 2024)
Damage to bridging veins could lead to disastrous complications during interhemispheric approaches. We investigated the morphological and histological characteristics of bridging veins. A total of 10 cadaveric heads and 86 patients were analyzed with either anatomic dissection or neuroimaging. The morphological features of the bridging veins and superior sagittal sinus were analyzed by the endoscope. The histology of the junction between the bridging veins and superior sagittal sinus was evaluated under the microscope with staining for H&E, elastic fiber, and Masson’s staining. We found three types of bridging vein configurations in the junction between the bridging vein and superior sagittal sinus: direct connection (type A), vein runs a certain distance below the dural wall tightly (type B), and vein runs a certain distance on the lateral sinus (type C). Valvular-like fibrous cords were present on the opening of type A, trabecular in type B, and arachnoid granules in type C. Loose connective tissue connected the venous wall and dura mater in type A, sinus wall forms the inner wall of the bridging vein in type B, bridging vein accompanied by arachnoid granules in the type C. This classification enables surgeons to predict various bridging vein configurations, followed by safely achieving the optimal dissection during interhemispheric approaches.